The Influences of Cavitation Effects on the Electric Conductivity of Juices in Sugar Production - Zheplinska, M.; Burova, Z.; Muchtruk, M.; Bal’-Prylypko, L. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The paper presents the results of studies the influence cavitation effects arising from the juices steam treatment on cellular and diffusion juices in sugar production. In conducting parallel studies the juices treatment by steam and their usual heating and cooling structural transformations in the constituent parts of juices have been established which leads to an increase in electric conductivity. Thus ion carriers are releasing which will allow to increase the juice purity and the sugar-sand production amount.
Keywords: cellular juice; diffusion juice; sugar production; electric conductivity; steam-condensation cavitation; macromolecular compounds; colloidal dispersion substances